2021
DOI: 10.3390/jcm10081761
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Changes in Quality of Life in Patients with Advanced Lung Cancer during In-Hospital Exercise Training and Chemotherapy Treatment: A Randomized Controlled Trial

Abstract: The aim of this study was to assess the impact of exercise training on the quality of life (QoL) of patients diagnosed with stage IIIB and stage IV non–small cell lung cancer (NSCLC) compared to a passive control group (CG). The exercise-trained group (ETG) consisted of 18 patients, and the CG consisted of 8 patients. The training program in the ETG consisted of two 2-week running cycles interspersed with consecutive rounds of chemotherapy with cytostatic drugs. A comparison of the changes in the Short Form (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…During this stage, three studies were excluded due to <70% of the population sample not having advanced-stage lung cancer ( n = 2) and absent control group ( n = 1). Two studies reported findings from the same trial but illustrated independent outcomes in each publication that were included [ 28 , 29 ]. Therefore, a total of 12 prospective studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this stage, three studies were excluded due to <70% of the population sample not having advanced-stage lung cancer ( n = 2) and absent control group ( n = 1). Two studies reported findings from the same trial but illustrated independent outcomes in each publication that were included [ 28 , 29 ]. Therefore, a total of 12 prospective studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the prospective studies selected demonstrated an overall low risk of bias for three studies [ 28 , 29 , 30 ], overall moderate risk of bias for eight studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and overall high risk of bias for one study [ 39 ] ( Table 1 ). All 12 studies reported a distinct random allocation sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health and mental wellbeing are important factors in cancer rehabilitation, as they directly affect the general rehabilitation process. The diagnosis, treatment, hospitalization, and prognosis of oncologic diseases generate stress, fear, and anxiety leading to a decrease in overall physical activity ( 40 ). Mental symptoms affect patients during all stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…So, self -efficacy has been advocated to support the needs of patients with lung cancer at these critical moments and reduce symptom burden to increase function. Evidence displays that mindfulness programs help to improve exercise capacity, breathlessness, tiredness, discomfort, psychosomatic distress, and quality of life (Rutkowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%